Characterization of Flavonoid Glycosides from Fenugreek (Trigonella foenum-graecum) Crude Seeds by HPLC–DAD–ESI/MS Analysis - Benayad, Zakia (Int J Mol Sci, 2014)
Fenugreek (Trigonella foenum-graecum) is a medicinal plant which is widely used for its pharmacological properties. In this study the phenolic composition of fenugreek crude seeds originating from Morocco has been investigated. Extraction was performed from defatted seeds by a hydromethanolic solution using an Accelerated Solvent Extractor. HPLC technique coupled to negative ion electrospray ionization mass spectrometry and diode array detection was employed to identify the polyphenol in the obtained extract. The obtained results allowed the detection of 32 phenolic compounds among which various flavonoid glycosides and phenolic acids have been tentatively identified on the basis of their UV and MS spectra, and comparisons with standards when available, as well as with literature data. A systematic study of the obtained MS spectra and the observed fragmentation showed that most of the identified compounds were acylated and non-acylated flavonoids with apigenin, luteolin and kaempferol as aglycons. Hydroxycinnamic acids mostly dominated by caffeic acid derivatives were also detected. The quantitative analysis of the identified compounds showed that the phenolic composition of the studied crude fenugreek seeds was predominantly acylated and non-acylated flavone derivatives with apigenin as the main aglycon.